2019
DOI: 10.1002/anie.201812687
|View full text |Cite
|
Sign up to set email alerts
|

C−C Bond Formation of Benzyl Alcohols and Alkynes Using a Catalytic Amount of KOtBu: Unusual Regioselectivity through a Radical Mechanism

Abstract: We report aC À Cb ond-forming reaction between benzyl alcohols and alkynes in the presence of ac atalytic amount of KO t Bu to form a-alkylated ketones in which the C = Og roup is located on the side derived from the alcohol. The reaction proceeds under thermal conditions (125 8 8C) and produces no waste,m aking the reaction highly atom efficient, environmentally benign, and sustainable.B ased on our mechanistic investigations,w ep ropose that the reaction proceeds through radical pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 41 publications
0
11
0
1
Order By: Relevance
“…A growing number of reports are appearing where the metals of the first main group are used in catalytic applications, for example, hydroboration, [3] intermolecular and intramolecular hydroamination, [4] hydrophosphination/hydrophosphorylation, [5] hydrosilylation, [6] hydrogenation, [7] dehydrogenation (or dehydrocoupling), [8] and Brønsted base catalysed CÀC additions. [9] For the last application, first reports date back to the 1950s from Pine and Wunderlich, who described the addition of alkylbenzenes to styrenes with catalytic amounts Organolithium compounds have been at the forefront of synthetic chemistry for over a century, as they mediate the synthesis of myriads of compounds that are utilised worldwide in academic and industrial settings. For that reason, lithium has always been the most important alkali metal in organometallic chemistry.…”
Section: Alkali Metals In Homogeneous Catalysismentioning
confidence: 99%
“…A growing number of reports are appearing where the metals of the first main group are used in catalytic applications, for example, hydroboration, [3] intermolecular and intramolecular hydroamination, [4] hydrophosphination/hydrophosphorylation, [5] hydrosilylation, [6] hydrogenation, [7] dehydrogenation (or dehydrocoupling), [8] and Brønsted base catalysed CÀC additions. [9] For the last application, first reports date back to the 1950s from Pine and Wunderlich, who described the addition of alkylbenzenes to styrenes with catalytic amounts Organolithium compounds have been at the forefront of synthetic chemistry for over a century, as they mediate the synthesis of myriads of compounds that are utilised worldwide in academic and industrial settings. For that reason, lithium has always been the most important alkali metal in organometallic chemistry.…”
Section: Alkali Metals In Homogeneous Catalysismentioning
confidence: 99%
“…9 Recently, benzylic alcohols were coupled with arylacetylenes in the presence of potassium tert-butoxide to form 1,3-diarylpropan-1ones. 10 In this transformation, a ketyl radical is believed to be formed from the alcohol based on experimental evidence and the radical then reacts with the alkyne followed by several hydrogen transfer reactions to generate the product. 10 Although, potassium tert-butoxide strictly serves as a base in this coupling, the alkoxide has also been shown to promote radical coupling reactions such as the formation of biaryls from aryl halides and arenes.…”
Section: Introductionmentioning
confidence: 99%
“…10 In this transformation, a ketyl radical is believed to be formed from the alcohol based on experimental evidence and the radical then reacts with the alkyne followed by several hydrogen transfer reactions to generate the product. 10 Although, potassium tert-butoxide strictly serves as a base in this coupling, the alkoxide has also been shown to promote radical coupling reactions such as the formation of biaryls from aryl halides and arenes. 11 Potassium tert-butoxide is a very commonly employed base for dehydrogenative transformations with alcohols where the mechanism either involves metal-catalyzed acceptorless dehydrogenation or Meerwein-Ponndorf-Verley/Oppenauer processes.…”
Section: Introductionmentioning
confidence: 99%
“…Experiment involving a radical trapping reagent (TEMPO) used on standard catalytic conditions provided the desired product in complete conversion and confirmed that free radical pathways are not involved in base catalyzed Michael addition reactions (Scheme a) . Further, reaction of p ‐tolylmethanol‐D with acrylonitrile provided quantitative conversion with 92 % of deuterium incorporation at α‐position to the nitrile and only minor amount of deuterium scrambling occurred resulting in 7 % of deuterium at β‐position (Scheme b).…”
Section: Resultsmentioning
confidence: 99%